Exploring the Head Versus Tail‐End Dichotomy on Yield and Farm Incomes in Smallholder Irrigation Schemes in Tanzania. Issue 5 (27th May 2019) - Manero, Ana; Wheeler, Sarah Ann; Zuo, Alec; Mdemu, Makarius
Abstract: Variations in water supply and their impact on farm production in smallholder irrigation schemes are often associated with the location of irrigators at either the head or tail‐end, with tail‐enders usually considered to be at a severe disadvantage. However, it is rare that the impact of multidimensional proxies of water (capturing adequacy, timing, and location) on farm production and income have been evaluated in conjunction with other relevant variables. Using GIS analysis, this study combines irrigation household surveys, irrigation area characteristics, and cadastral data from two smallholder irrigation schemes in southern Tanzania. The results indicate that location at both the head‐end and tail‐end had a negative significant impact on farm yields, but not farm incomes. Also, being further downstream the secondary canals (but not necessarily away from the system's intake) had a significant negative effect on both yields and incomes. Surprisingly, increased tomato production drove a decline in incomes, thus raising the importance of crop selection and productivity barriers linked to markets and knowledge. In absence of actual quantitative measures of water supply, this study concludes that using a multidimensional water proxy can uncover important effects that would otherwise remain overlooked by the widespread head versus tail‐end dichotomy, commonly used in the study of water distribution within smallholder irrigation systems. Plain Language Summary: In most low‐technology, smallholder irrigation schemes, no accurate measures of physical water supply are available. Thus, a common alternative in the literature is to use head‐end and tail‐end locations within the schemes as proxies for "good" or "bad" irrigation water supply. However, other aspects of water supply (e.g., location along the distributary canals and irrigation scheduling) may also have an impact on irrigated production. Thus, this study proposes a multidimensional approach where various water‐related factors are evaluated in conjunction with socioeconomic and farm variables to understand their effects on crop yields and incomes. Based on two smallholder irrigation schemes in southern Tanzania, this study found that various water factors are critical for crop yields, but less so for incomes from irrigated crops. The results of this study suggest that water supply within smallholder schemes is better understood through its multiple aspects, rather than limited to the unidimensional head versus tail‐end dichotomy. Key Points: GIS and regression analyses were used to evaluate the effect of several water proxies on irrigated production in two smallholder schemes Head and tail‐end locations had negative effects on rice yields, while proximity to the main canal increased both yields and incomes The varied effects of farm location, water satisfaction, and supply scheduling reinforce the need to consider multidimensional water proxies